CHALLENGES AND PROSPECTS OF EURASIAN INTEGRATION (ILLUSTRATED BY EAEU) - Olga A. Grishina; Sergey G. Evsyukov; Elena V. Ustyuzhanina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the prospects of developing integration processes within the frames of the Eurasian Economic Union. Topicality of this problem can be explained by complicated economic situation within which common markets of goods, capital and labour are formed, availability of institutional barriers to integration, low competitiveness of economies that unite on the global market. Resource potential of EAEU is investigated, trade links between country-members are analyzed, promising cooperation projects are considered. On the basis of such analysis a conclusion is made about a clear dominance of Russia as a central link of the Union not only by absolute indicators (supply of resources and output) but by the share in trade balance of partners, volumes of direct investment and positions in value chains. The authors show that barriers on the way of effective integration are formed not only by objective difficulties of combining heterogeneous economics but by mistakes in managing integration processes, in particular poor use of software-target approach, mistakes in goal-setting, ignoring the current problems of balancing budget-taxation and cash-credit policies.